1983
DOI: 10.3382/ps.0621830
|View full text |Cite
|
Sign up to set email alerts
|

Lipogenesis and Lipolysis in Normal and Dwarf Chickens from Lines Selected for High and Low Body Weight

Abstract: Lipogenic and lipolytic comparisons were made among normal and dwarf adult males from both high-weight (HW) and low-weight (LW) selected lines. Six nonfasted birds from each of the four populations were sacrificed, and in vitro lipogenesis and lipolysis were measured in liver, adipose, and bone tissue. Also determined were activities of acetyl CoA carboxylase (E.C.6.4.1.2), NADP-malate dehydrogenase (E.C.1.1.1.40), ATP-citrate lyase (E.C.4.1.3.8), and plasma-free fatty acids (FFA). In comparison with the HW ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
1

Year Published

1985
1985
1994
1994

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 31 publications
2
14
0
1
Order By: Relevance
“…The results of this experiment in which chicks were examined at 28 days of age were consistent with those obtained with adult chickens (Calabotta et al, 1983). At both ages, chicks from the LW line exhibited increased lipogenic and lipolytic capacities when compared to their HW counterparts.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The results of this experiment in which chicks were examined at 28 days of age were consistent with those obtained with adult chickens (Calabotta et al, 1983). At both ages, chicks from the LW line exhibited increased lipogenic and lipolytic capacities when compared to their HW counterparts.…”
Section: Discussionsupporting
confidence: 69%
“…Calabotta et al (1983) compared lipogenic and lipolytic capacities between adult males from two divergent lines developed through selection for body weight at 8 weeks of age (Siegel and Cherry, 1981). Their results suggested that, at least in mature males, lipid turnover differed between these lines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The skeleton is known to be an important lipogenic site in the fowl (Nir and Lin, 1982;Calabotta et al, 1983). The higher fat content in the tibia bone of the LF line has been confirmed in other studies (unpublished observations) and suggests that lipogenesis in the skeleton of LF birds is higher, or that the mobilisation from this site to the adipose tissues is lower compared with the HF birds.…”
Section: Discussionsupporting
confidence: 56%
“…Nitsan et al (1991 ) GIT would be inefficient in digesting it during the first few days after hatch. In intact chickens, Calabotta et al (1983Calabotta et al ( , 1985 (Nitsan et al, 1991;Nir and Levanon, 1993) and the chick had changed from primarily a lipidbased to a carbohydrate-based metabolism with external food sources (Duke, 1984 …”
Section: Introductionmentioning
confidence: 99%